Sistem Penggajian di CV. Pusaka Bali Persada - ERAWAN, NI PUTU ADELIA SARASWATI; USTRIYANA, I NYOMAN GEDE; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.3, Juli 2019, 2019)
Payroll System at CV. Pusaka Bali Persada Every company really needs the role of human resources in carrying out its business activities and must be managed properly. Human resources function to improve the effectiveness and efficiency of a company as a function in the company. One way to get competing human resources is to pay attention to the payroll system in a company. The payroll system itself aims to attract employees, retain employees, and motivate employees. This research was conducted at CV. Bali Persada Heritage which is determined intentionally. Sampling using techniques with census methods. The number of samples is 12 respondents consisting of top managers and middle managers. This study uses qualitative descriptive analysis. The results showed that the salaries of employees at CV. Pusaka Bali Persada consists of basic salary and benefits. CV. Pusaka Bali Persada provides basic salary by referring to the District / City Minimum Wage (UMK) that has been set by the government. Paying is done with a payroll administration system. The results of this study also show that the determinants of payroll system in CV. Pusaka Bali Persada includes payroll techniques, payroll procedures, payroll structure, payroll openness, government support, and payroll policies. The majority of top managers and middle managers agree with the payroll system that has been applied by CV. Pusaka Bali Persada.